Rapid Fabrication of Glass Micro and Nanostructures via Laser-assisted Hot Embossing - Lee, Helen May Shian; Ismayuzri, Ishak; Mohd Zairulnizam, Mohd Zawawi (Japan Laser Processing Society, 2023)
The escalating demand for glass that exhibits various surface functions has encouraged efforts to develop more efficient and economical micro-/nano-patterning of glass substrates. We propose rapid hot embossing of glass micro-/nanostructures using an infrared transmissive mold assisted by CO2 laser irradiation. This resistless, etch-free technique utilizes the synergy of the silicon mold’s high transmittance and strong optical absorption of the glass at a 10.6-μm wavelength. Furthermore, this non-isothermal process requires preheating of the glass temperature below the glass transformation point (Tg) of the glass, eliminating the soaking time, and using a short contact pressing time and a lower pressing load to produce high-resolution space patterns. The method is capable of instantaneous high-resolution replication of various grating patterns from the nano- to microscale with a single laser scan. By controlling the scanning speed and ensuring sufficient pressure and heating depth on the glass surface, 250-nm to 50-μm line- widths and space patterns were embossed in a few seconds with excellent replication fidelity. The laser-assisted hot embossing methods developed in this study facil-itated high-throughput, energy-efficient, reproducible, and highly accurate micro-/nano-patterning of glass surfaces.